Single-Photon Emission Computer Tomography Imaging of Prostate-Specific Membrane Antigen (PSMA) Expression in Prostate Cancer Patients Using a Novel Peptide-Based Probe [99mTc]Tc-BQ0413 with Picomolar Affinity to PSMA: A Phase I/II Clinical Study; ACS Pharmacology & Translational Science; Vol. 8, iss. 3 - Medvedeva А. А. Anna Aleksandrovna; Chernov V. I. Vladimir Ivanovich; Larkina M. S. Mariya Sergeevna; Rybina A. N. Anastasiya Nikolaevna; Zelchan (Zeltchan) R. V. Roman Vladimirovich; Bragina O. D. Olga Dmitrievna; Varvashenya R. N. Ruslan Nikolaevich; Zebzeeva O. S. Olga Sergeevna; Bezverkhnyaya E. A. Ekaterina Aleksandrovna; Tolmachev V. Vladimir; Orlova A. Anna (2025, 2025)
Title screen